Respuesta :
First we have to find (f o g)(x):
(f o g)(x) = [2(7x + 1) + 2] = (14x + 2 + 2) = 14x + 4
Then we have to find (g o f)(x):
(g o f)(x) = [7(2x + 2) + 1] = (14x + 14 + 1) = 14x + 15
Comparing both the results:
(g o f)(x) > (f o g)(x)
According to above explanation,
D.g(f(x)) produces the greatest output, is the correct answer.
(f o g)(x) = [2(7x + 1) + 2] = (14x + 2 + 2) = 14x + 4
Then we have to find (g o f)(x):
(g o f)(x) = [7(2x + 2) + 1] = (14x + 14 + 1) = 14x + 15
Comparing both the results:
(g o f)(x) > (f o g)(x)
According to above explanation,
D.g(f(x)) produces the greatest output, is the correct answer.
The answer is the fourth option "g(f(x)) produces the greatest output."
How:
- [tex] (f o g)(x) = [2(7x + 1) + 2] = (14x + 2 + 2) = 14x + 4 [/tex]
- [tex] (g o f)(x) = [7(2x + 2) + 1] = (14x + 14 + 1) = 14x + 15 [/tex]
Looking at both equations you would see that (g o f)(x) > (f o g)(x) so the answer is the fourth option!
Hope this helps!